Immune Cell Hacking: Challenges and Clinical Approaches to Create Smarter Generations of Chimeric Antigen Receptor T Cells - Elahi, Reza; Khosh, Elnaz; Tahmasebi, Safa; Esmaeilzadeh, Abdolreza (Frontiers in Immunology, 2018)
Abstract T cells equipped with chimeric antigen receptors (CAR T cells) have recently provided promising advances as a novel immunotherapeutic approach for cancer treatment. CAR T cell therapy has shown stunning results especially in B-cell malignancies; however, CAR T cell therapy has shown less success against solid tumors, which is more supposed to be related to the specific characteristics of the tumor microenvironment. In this review, we discuss the structure of the CAR, current clinical advantages from finished and on-going trials, adverse effects, challenges and controversies, new engineering methods of CAR T cells, and clinical considerations that are associated with CAR T cell therapy both in hematological malignancies and solid tumors. Also, we provide a comprehensive description of recently introduced modifications for designing smarter models of CAR T cells. Specific hurdles and problems that limit the optimal function of CAR T cells especially on solid tumors and possible solutions according to new modifications and generations of CAR T cells have been introduced here. We also provide information of the future directions on how to enhance engineering the next smarter generations of CAR T cells in order to decrease the adverse effects and increase the potency and efficacy of CAR T cells against cancer